Micronutrient deficiency among patients with ulcerative colitis - Amany Hussien; Sawsan Abd El-Moniem; Ziyad Tawhid; Ahmed Altonbary (SpringerOpen, 2022)
Abstract Background and aim Malnutrition is a common problem among patients with inflammatory bowel disease and up to 18-62% of ulcerative colitis (UC) patients were reported to be malnourished. This study aimed to assess micronutrient status among naïve UC patients and its correlation with disease severity. Methods A prospective case-control study carried out on 46 patients who visited our endoscopy unit between April 2019 and April 2021. The patients were classified into 3 groups of mild, moderate, and severe UC based on colonoscopy findings, and histopathological examination. Serum was collected and assayed for levels of iron, magnesium, zinc, selenium, and copper. Results Forty-six (17 male, 29 female) patients divided into 2 groups (23 naïve UC patients and 23 healthy individuals) with the mean age of 32 years were included in the study. The serum levels of magnesium, zinc, and selenium were significantly lower in the UC group (p < 0.001, 0.018 and < 0.001, respectively). However, iron and copper levels were not significantly different between the 2 groups. In discriminating severe from mild-moderate UC cases, there was a statistically significant result of magnesium at cutoff 1.8 or less in discriminating severe from mild to moderate UC cases with an AUC of 0.950 and p value of < 0.001. Conclusion Micronutrients should be assessed in patients in UC patients to alert to the fact that correction of these deficiencies could facilitate achievement of remission. Further research is needed to confirm if magnesium levels could serve as a predictor of the disease severity.